1989
DOI: 10.1007/bf01311084
|View full text |Cite
|
Sign up to set email alerts
|

Relatedness of glycoproteins expressed on the surface of simian herpesvirus virions and infected cells to specific HSV glycoproteins

Abstract: The antigenic relatedness of the surface glycoprotein antigens of six herpesviruses indigenous to human and nonhuman primates was examined. Binding of anti-viral sera to viral antigens expressed on the surface of infected cells demonstrated that the surface antigens of herpes simplex virus type 1 (HSV 1), HSV 2, simian agent 8 (SA8), and Herpesvirus simiae (B virus) exhibit extensive cross-reactivity. Surface antigens of two viruses isolated from South American primates, H. saimiri 1 (HVS 1) and H. ateles 1 (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
37
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 55 publications
5
37
0
Order By: Relevance
“…Such highly conserved regions undoubtedly represent important structural and/or functional regions of these proteins, indicating that these proteins have structures and functions similar to those of their HSV homologs. This is also consistent with the extensive antigenic cross-reactivity observed between almost all HSV, SA8, HVP-2, and BV proteins (10,12,17). Finally, genotypic sequence variation among BV isolates was minimal in nonglycoproteins but readily evident in the glycoproteins except for the conserved gD glycoprotein.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…Such highly conserved regions undoubtedly represent important structural and/or functional regions of these proteins, indicating that these proteins have structures and functions similar to those of their HSV homologs. This is also consistent with the extensive antigenic cross-reactivity observed between almost all HSV, SA8, HVP-2, and BV proteins (10,12,17). Finally, genotypic sequence variation among BV isolates was minimal in nonglycoproteins but readily evident in the glycoproteins except for the conserved gD glycoprotein.…”
supporting
confidence: 70%
“…When transmitted to nonmacaque primates, BV produces severe infections which usually involve the central nervous system and are frequently fatal (31,37,38). The molecular basis for the extreme neuropathology of BV in nonmacaque species is an intriguing question that remains unanswered.While sequences for a number of genes of BV have been reported (3,9,23,34,35,37), genomic characterization of BV has largely been limited to restriction analysis and gene mapping by hybridization with HSV gene probes (10,16,17). Such studies have suggested that, for the most part, the BV genome is colinear with that of HSV.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Stress induces reactivation of the viruses from the latent state, resulting in shedding of infectious viruses from mucosal tissue (14,35). In addition, herpes B virus shows strong serological cross-reactivity with HSV (5,18). The genetic arrangement is almost identical between herpes B virus and HSV (8,21,22,25), and the nucleotide sequences of the herpes B virus genes have been reported to show high homology with the corresponding HSV genes (1,21,22,25).…”
mentioning
confidence: 99%
“…SA8, herpes simplex virus (HSV), B virus (which is indigenous to the rhesus monkey) and bovine herpesvirus 2 (BHV-2) (the causative agent of bovine herpes mamillitis) show identical genome structure, nucleotide sequence similarities and antigenic cross-reactivity (Desrosiers & Falk, 1981;Eberle et al, 1989;Hammerschmidt et al, 1988;Honess, 1984;Ludwig et al, 1983;Malherbe & Harwin, 1958;Sterz et al, 1973/74;Stevens et al, 1968). Based on these common features, these viruses were grouped to form the Simplexvirus genus (Brown, 1986;Roizman et al, 1981).…”
mentioning
confidence: 99%